2021
DOI: 10.3389/fphys.2021.755923
|View full text |Cite
|
Sign up to set email alerts
|

Manual Therapy With Rest as a Treatment for Established Inflammation and Fibrosis in a Rat Model of Repetitive Strain Injury

Abstract: Background: Repetitive strain injuries caused by repetitive occupational work are difficult to prevent for multiple reasons. Therefore, we examined the effectiveness of manual therapy (MT) with rest to treat the inflammation and fibrosis that develops through the performance of a repetitive task. We hypothesized that this treatment would reduce task-induced sensorimotor declines and neuromuscular inflammation.Methods: Twenty-nine female Sprague-Dawley rats performed a reaching and lever-pulling task for 14week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We also added direct manipulation of the palm in this study, where the tip of the rat’s index finger was pressed into the palm at and just distal to the transverse carpal ligament with a rolling motion. The individuals providing these treatments were the same as in previous studies [ 19 , 20 ]. Treatments to TASK-MT rats were performed 3 times per week on alternate days to the task performance for 7 weeks and lasted approximately five to seven minutes per limb, i.e., a total of 10–14 min per rat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also added direct manipulation of the palm in this study, where the tip of the rat’s index finger was pressed into the palm at and just distal to the transverse carpal ligament with a rolling motion. The individuals providing these treatments were the same as in previous studies [ 19 , 20 ]. Treatments to TASK-MT rats were performed 3 times per week on alternate days to the task performance for 7 weeks and lasted approximately five to seven minutes per limb, i.e., a total of 10–14 min per rat.…”
Section: Methodsmentioning
confidence: 99%
“…GraphPad PRISM version 9 was used for the statistical analyses. The sample size for this study was derived from our previous studies [ 20 , 22 ], assuming a power of 80% and level of significance of 0.05, and a standard deviation of 28 for grip strength. All data are expressed as mean ± 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual traction improves the ROM and flexibility with a relaxing position, which is characterized by the relaxation of surrounding tissues as much as possible and the largest space in the capsule 24,25 . Manual traction improves neuromuscular inflammation and fibrosis of upper limbs in a rat model of repetitive strain injury 26 . There are few reports in the literature on manual traction in rat knee contracture model.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that between 20 and 40% of UC patients used tuina to alleviate the unbearable symptoms ( Rawsthorne et al, 2012 ; Oxelmark et al, 2016 ). However, the effective mechanism of tuina therapy is still in its infancy, several studies found that tuina can down-regulate the expression levels of tumor necrosis factor-α, interleukin (IL)-6, and IL-10 to reduce inflammation, suggesting that tuina plays an effective role in immune or inflammatory diseases ( Mori et al, 2004 ; Crane et al, 2012 ; Negahban et al, 2013 ; Barbe et al, 2021 ). Furthermore, enrichment for diversity and beneficial bacterial community was observed in rats after tuina treatment, it is indicated that tuina exerts an immunomodulatory effect by modulating the microbiota ( Zhu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%